Інтелектуальна краудінвестингова платформа як інструмент стимулювання розвитку смарт-підприємств - Сердюк, О.С. (Економіка промисловості, 2025)
У статті обґрунтовано концепцію краудінвестингової платформи як інструменту зниження трансакційних витрат, що обмежують інвестиційну активність у сфері смарт-виробництва. Проаналізовано ключові бар’єри залучення інвестицій — інформаційну асиметрію, складність контрактів й адміністративні перешкоди. Запропоновано функціонал цифрової платформи, спроможної забезпечити прозорість, довіру між контрагентами та ефективну взаємодію з державними органами. This article presents a theoretical and applied framework for developing an intelligent crowdfunding investment platform as a key institutional tool for supporting the growth of smart enterprises in the context of Industry 4.0. The relevance of this research lies in the contradiction between the high economic efficiency of smart manufacturing models and the low pace of their diffusion in emerging economies, particularly in Ukraine. Despite their potential to boost productivity, optimize resources, and increase adaptability to market changes, smart enterprises remain underfinanced due to a lack of investor confidence and excessive transaction costs. The paper analyzes these transaction costs through the lens of neoclassical and institutional economic theories. It identifies several major inhibitors to investment in high-tech production: information asymmetry, distrust among market participants, opportunistic behavior of contractors, and complex administrative procedures. While classical theory points to low labor costs as a key barrier to automation, real-world evidence from China, Bangladesh, and Morocco suggests that other factors — such as global supply chain integration, state subsidies, reputational pressures, and skilled labor shortages — may override the wage factor and stimulate investment in smart manufacturing even in low-wage environments. To address these constraints, the article proposes a multi-layered digital platform that combines financial, informational, legal, and reputational functions. The platform is expected to provide real-time operational data from smart factories (via IoT sensors), AI-based analytics, reputation scoring, blockchain-secured transactions, smart contract generation tools, and integration with public registries. In doing so, it acts not only as a financial intermediary, but as a digital institution that improves transparency, reduces uncertainty, and fosters trust between investors and project owners. The study concludes that the implementation of such a platform would significantly lower the transaction costs associated with financing smart enterprises, thus enhancing their attractiveness to private investors and accelerating the digital transformation of industrial sectors.